Women founders in the technology industry: The startup-relatedness of the decision to become a mother - Katherina Kuschel (Administrative Sciences, 2019)
This paper explores the decision to become a mother among women in the technology industry, particularly if there is an "optimal context" regarding startup development (business stage and size). Eighteen interviews were conducted with an international sample of women founders and analyzed using a grounded theory approach. Findings suggest two sources of "mumpreneurs" in technology ventures: (1) women who created a startup while young and childless, postponing maternity until the business is "stable"; and (2) mothers who created a technology venture as a strategy to gain higher levels of flexibility and autonomy than they experienced in the corporate world. The first group is highly work-role salient, while the second is highly family-role salient. The results of this work contribute to theory development by revealing the "startup-relatedness" of family decisions by women founders in the technology industry. I offer recommendations of how accelerators can improve mentorship for women in high-growth technology ventures and unleash women's potential.
Keywords: 350; entrepreneurship; new high-technology ventures; women founders; motherhood; decision-making; role salience; mumpreneurs; startups